Selective Functional Interaction Between the Lateral Habenula and Hippocampus During Different Tests of Response Flexibility - Baker, Phillip M.; Rao, Yingxue; Rivera, Zeena M. G.; Garcia, Esteli M.; Mizumori, Sheri J. Y. (Frontiers in Molecular Neuroscience, 2019)
The lateral habenula (LHb) has been shown to play critical roles in a variety of appetitive tasks (e.g. spatial memory and object recognition) that require animals to flexibly respond to changing task conditions. These types of tasks are known to be dependent on hippocampus (HPC) and/or medial prefrontal cortex (mPFC), suggesting that the LHb contributes to the limbic memory circuit. Here we provide new evidence that the LHb and HPC play distinct but complimentary roles in tasks that require flexible responding to changing task conditions. Experiment 1 tested whether the LHb is needed for the performance of a HPC-dependent maze-based spatial delayed alternation task. The importance of interactions between the LHb and HPC to accomplish the same spatial delayed alternation task was tested in Experiment 2 where the LHb and HPC were disconnected both ipsilaterally and contralaterally. Experiment 3 tested LHb’s involvement in a standard behavioral economic task that requires flexible responding (maze-based delayed discounting), a task previously shown to rely on HPC. Results of Experiment 1, revealed that LHb inactivation impairs spatial delayed alternation during asymptotic performance but not during initial learning. Importantly, working memory did not appear to be affected as performance remained above chance levels both during initial learning and asymptotic testing. Experiment 2 showed that ipsilateral and contralateral disconnection of the LHb and HPC led to impaired performance on the spatial delayed alternation task. Impairments were not observed after unilateral inactivation of only one structure. Results of Experiment 3 were similar to our previous report of the effects of HPC inactivation: LHb inactivation impaired delayed discounting. All effects could not be accounted for by changes in reward magnitude discrimination, reward location per se, or sex of the animal. These findings, combined with other recent publications confirms and extends our working hypothesis that the LHb enables adaptive and flexible responding, particularly when established rules must be flexibly applied on a trial by trial basis. Since there are no known direct anatomical connections between LHb and HPC, future research is needed to understand how these structures communicate to enable flexible and rapid responding.